Criteria, Probability and Degree of Instability of Employment Taking into Account the Features of the Russian Labour Market - Vyacheslav Nikolaevich Bobkov; Vadim Grigoryevich Kvachev; Natalya Viktorovna Loktyukhina; Marco Ricceri (Экономика региона, 2017)
The article reveals the issues of the global character of precarization and substantiates the criteria of precarious employment taking into account its special aspects in Russian Federation. The existing variability of approaches to the definition of precarious employment and the necessity to elaborate its optimal criteria in view of features of national labour have conditioned the relevance of the research. The paper involves international and Russian research on precarity and significantly uses the results of expert survey conducted by the authors in autumn 2016. The experts have considered groups of criteria based on: labour contract term, nature of labour relations, precarious terms of work. The experts also were asked to evaluate different forms of employment in which precarity may exert. As a result of the conducted research, we have elaborated the generalized criteria, which identify various forms of instability in labour market. The authors put forward a hypothesis that the criteria of the International Labour Organization (ILO) need to be adapted to the Russian realities when determining unstable employment, and the phenomenon of precarious employment has to be defined from the point of view of the probabilistic nature of its various manifestations. Based on the results of the research, the authors have qualified the relevance of International Labour Organization’s (ILO) criteria in the Russian context. We also have substantiated the probable character of precarious employment and defined probability of precarity exertion in the flexible forms of employment. The set of precarious employment criteria is specified in accordance with Russian context: we have clarified and complemented them, and defined the probability of precarity exertion in different forms of employment. The main result of the research is the structure of criterial standards, which identifies precarious employment.The conceptual issues and findings of the paper can be used as a theoretical and methodological basis to identify the scale of precarious employment in Russia as well as to evaluate precarity exertion in individual workplace.